2006
DOI: 10.2987/8756-971x(2006)22[147:froaai]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

First Record of Aedes Albopictus in Croatia

Abstract: The first record of Aedes albopictus in Croatia was made in Zagreb, Croatia, on October 28, 2004. A total of 13 larvae were collected in a discarded ceramic toilet bowl in a forested area in the southwest suburbs. Because the winter temperatures in Zagreb are not favorable for survival, this finding of Ae. albopictus may be temporary. Its survival in northern Croatia remains to be studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 1 publication
0
25
0
5
Order By: Relevance
“…In general, the purpose of mosquito monitoring lies in faunal characteristics, the daily and seasonal dynamics and abundance, defining the areas with mosquito annoyance and determining potential vectors of diseases. Out of the total of 50 mosquito species recorded in Croatia Klobučar et al 2006;Žitko & Merdić 2006), 20 have been found in the area of the city of Osijek (Merdić 1996;Merdić & Lovaković 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the purpose of mosquito monitoring lies in faunal characteristics, the daily and seasonal dynamics and abundance, defining the areas with mosquito annoyance and determining potential vectors of diseases. Out of the total of 50 mosquito species recorded in Croatia Klobučar et al 2006;Žitko & Merdić 2006), 20 have been found in the area of the city of Osijek (Merdić 1996;Merdić & Lovaković 2001).…”
Section: Introductionmentioning
confidence: 99%
“…albopictus in the Zagreb area was made in October 2004 during the regular inspection of the mosquito breeding sites. Mosquito larvae were found and collected from an artificial container in a forest located in the western suburb of the city [46]. This was also the first finding of Ae.…”
Section: Aedes Albopictusmentioning
confidence: 65%
“…In Croatia, a total of 51 species of mosquitoes have been described so far [45][46][47][48]. In the City of Zagreb, 30 mosquito species have been detected [46,[49][50][51][52][53][54][55][56][57] In the indoor breeding sites of Zagreb the species Cx.…”
Section: Mosquitoes (Diptera Culicidae) In the Zagreb Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The Indian man developed a febrile syndrome two days after his arrival in Italy and also had high titres of antibodies against Chikungunya. The phylogenetic analysis showed that the strain that caused Italian outbreak was similar to the strains detected on the Indian subcontinent (Yergolkar et al, 2006) (Klobucar et al, 2006), two cases of indigenous dengue were diagnosed also in 2010 (Schmidt-Chanasit et al, 2010;Gjenero-Margan et al, 2011). The identification of these cases of dengue fever and Chikungunya occurred in 2010, which were in all cases well clustered in space and time, is strongly suggestive that autochthonous transmission of tropical viruses in Europe is ongoing.…”
mentioning
confidence: 71%